Le rôle de la levure saccharomyces cerevisiae dans la fermentation des produits alimentaire - SAKHER, Fatima Zohra; KASSOUS, Halima (My University, 2021)
Dates Can Be defined as the fruit of the desert. The latter can be valued for the development of desert agriculture in Algeria and in the countries of North Africa by transforming them. Indeed, converting dates by biotechnological methods allows to obtain new products with added value and easy on the market, the most important of which is perhaps date juice. Date juice contains a high percentage of sugar, which can be a suitable medium for yeasts characterized by alcoholic fermentation from the transformation of sugar into alcohol. In our research, we isolated several yeasts from three different types of Algerian dates, including Deglet Nour. The results are positive, and Deglet Nour contains the yeast of the genus Saccharomyces cerevisiae. This can be explained by the nature of Deglet Al-Noor dates, which are rich in sugars, and are considered a suitable living environment for the yeast Saccharomyces cerevisiae.
Keywords: Saccharomyces cerevisiae, Yeast, fermentation, date